Concluding Considerations and Directions for Future Research - Cabigiosu, Anna (Digitalization in the Luxury Fashion Industry, 2020)
luxury fashion firms compete in an environment in which two different sets of competitive variables, traditional and new, coexist. However, these two sets are coherent and complementary within their own boundaries and less so with each other and challenge firms willing to design a new competitive landscape; luxury fashion firms are tightropes in between zeroing the brand and respecting the heritage; in between craftmanship, increased number of collections and sustainability; in between street style, increased number of collections and perception of uniqueness and rarity; and in between speed and creativity; additional studies are needed to understand how Maisons will cope with the above trade-offs, which variables will lead to superior competitive advantage, how new technologies and their usage will shape competitive advantaged.